Patriarchal Hegemony and Poverty in Child Marriage Practices in a Rural-Urban Area of Bandung City - Putri Nurfitriati Iswardani; Budi Radjab; Budiawati Supangkat (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
In Indonesia, child marriage is a time-honored custom, particularly among the poor. This tendency mixes with solid traditions and religions that are difficult to eradicate. The fight to eliminate child marriage must be continued even though it intersects with numerous problems, particularly for the children (women) involved. Inequality in the distribution of work, exploitation, and discrimination against offenders of child marriage are primarily caused by ideas that place children and women in subordinate positions as human beings. This study then discusses how patriarchy and its hegemony arose as an extension of power, giving rise to a dominant viewpoint that supports the maintenance of child marriage. An excerpt from ethnographic notes gathered by the author from the results of in-depth interviews with various subjects who have married before 18 and have a history of poverty in Bandung also becomes quite significant in this article. This research concludes, "When child marriage occurs within the context of poverty, then, rather than being a solution, this will lead perpetrators to the possibility of poverty reproduction, both structurally and culturally".